TUMPEK WARIGA AS AN ECOLOGY BASED LOCAL GENIUS IN SUPPORTING SUSTAINABLE TOURISM (CASE STUDY OF PLAGA VILLAGE, BADUNG, BALI) - Narrarya Narottama; I Ketut Suarja; Denok Lestari (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
As an international tourist destination, Bali has always been a main target of modern capitalists, both domestic and international. Massive construction of tourism facilities occurred in Bali, which directly affects and threatens the environment and changing social patterns of local communities. It is an irony, because Bali’s tourism relies on environment sustainability, natural landscapes and it’s unique cultural richness. Tumpek Wariga is one of the Balinese’s local genius, particularly in the context of maintaining harmony with all creatures, nature and environment, in form of cultural activitiesor Hindu rituals. These activities are summarized in Bali sublime philosophy which is recognized by UNESCO, namely the Tri Hita Karana. In various region of Bali, Tumpek Wariga is also called Tumpek Pengarah, Tumpek Uduh and Tumpek Bubuh. In this ceremony, the offerings are dedicated to the presence of Ida Sang Hyang Widhi (The Almighty God) in His manifestation as Lord Sangkara (Lord Shiva), the ruler of vegetation and environment in Balinese tradition. The purpose of this study was to assess the ultimate meaning and the implementation of Tumpek Wariga as a Balinese local genius in supporting ecological-based sustainable tourism in Bali. This case study took place in Plaga Village, which is one of the tourist villages developed by the government of Badung regency. This research uses qualitative approach, with data collection methods such as observation, in-depth interview and literature study. Hopefully, this research can be beneficial to all stakeholders and academics of tourism, especially in studies of Balinese local genius, as well as a new reference for the development of ecological based sustainable tourism in Bali.